Effects of Anchovy Head Meal and Rice Bran on KUB-2 Chickens - Irwan Setyo Nugroho; Ali Mursyid Wahyu Mulyono; Muhammad Husein (Jurnal Biologi Tropis, 2026)
This study addressed the increasing cost of conventional feed ingredients by evaluating local alternative feed resources for KUB-2 chicken production. Although anchovy heads (Stolephorus sp.) and rice bran have shown potential as low-cost feed ingredients, their combined substitution effects on KUB-2 chickens have not been previously investigated. This study aimed to evaluate the effects of substituting anchovy heads and rice bran in the diet on feed intake, body weight gain, feed conversion ratio, and mortality of KUB-2 chickens. The experiment used a Completely Randomized Design with three treatments: T0 (0% substitution), T1 (5% substitution), and T2 (10% substitution), each with four replications, resulting in 12 experimental units. Data were analyzed using analysis of variance followed by Duncan’s multiple range test. The results showed that substitution up to 10% had no significant effect (P>0.05) on all measured parameters and tended to maintain growth performance and feed efficiency. This indicates that the nutrient contribution of anchovy heads and rice bran was sufficient to support normal physiological growth without adverse effects on survival. These findings demonstrate that anchovy heads and rice bran can serve as practical local feed alternatives for partial replacement of conventional ingredients, offering potential feed cost efficiency while maintaining productive responses in KUB-2 chickens. Further studies using higher inclusion levels are recommended to determine the optimal biological and economic substitution threshold.